(untitled) (KULT_online, 2009)
In his 2007 monograph Mark Greengrass deals primarily with the reform effort of the French court under the reign of Henri III in the 1570s and 1580s. The attempt of Henri and his court to reorganise the central and regional administrations and to stabilise the tense situation between Catholics and Protestants was based on moral philosophy discussed at sessions of the king’s Palace Academy. Confronted with a wide range of religious, social and local interests, the ambitious royal initiatives were doomed to failure. Greengrass presents the story of a failed reform as a concise and highly convincing history of ideas in concrete political context.